Kriteria Pengembangan Ternak Sapi Berkelanjutan di Kabupaten Takalar - Paly, Basir (AL-Fikr, 2013)
This study aims to analyze the criteria of stakeholders in the development of sustainable cattle. By using participatory rural Appraisal (PRA), 35 samples of multi-stakeholder has observed, the data and information gatheredthrough focus group discussion Â technique (Focus Group Discussion) among stakeholders.